(untitled) (Clinics, 2011)
OBJECTIVES: To study the role of angiogenesis and cyclooxygenase-2 expression in cartilaginous tumors and correlate these factors with prognosis. INTRODUCTION: For chondrosarcoma, the histological grade is the current standard for predicting tumor outcome. However, a low-grade chondrosarcoma can follow an aggressive course-as monitored by sequential imaging techniques-even when it is histologically indistinguishable from an enchondroma. Therefore, additional tools are needed to help identify the biological potential of these tumors. The degree of angiogenesis that is induced by the tumor could assist in this task. Angiogenesis can be quantified by measuring the expression of vascular endothelial growth factor and CD34, and cyclooxygenase-2 can induce angiogenesis by stimulating the production of proangiogenic factors. METHODS: In total, 21 enchondromas and 58 conventional chondrosarcomas were studied by examining the clinical and histopathological findings in conjunction with the immunostaining markers of angiogenesis and cyclooxygenase- 2 expression. RESULTS: The significant variables that were associated with poor outcome were 1) higher-grade chondrosarcomas, 2) tumors that developed in flat bones, and 3) over-expression of CD34 (with a median count that was higher than 5.9 vessels in 5 high power fields). Moreover, CD34 expression (measured using the Chalkley method) revealed significantly higher microvessel density in flat bone chondrosarcomas. DISCUSSION: Previous studies have shown a positive correlation between Chalkley microvessel density and histological grade; however, in our sample, we found that the former is predictive of the outcome. Chondrosarcomas in flat bones have been shown to correlate with a poor prognosis. We also found that CD34 microvessel density values were significantly higher in flat-bone chondrosarcomas. This could explain-at least in part-the more aggressive biological course that is taken by these tumors. CONCLUSIONS: These results provide evidence that CD34 microvessel density in chondrosarcomas can be helpful in predicting patient outcome and may add to our understanding of chondrosarcoma pathogenesis.